PENGARUH FIRM SIZE, GROWTH OPPORTUNITY DAN NET WORKING CAPITAL TERHADAP FIRM VALUE PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI DENGAN CASH HOLDING SEBAGAI VARIABEL INTERVENING - Putra, Wirandra Oktavian Arief; Arief, Mohammad Yahya; Syahputra, Hendra (Fakultas Ekonomi dan Bisnis, 2024)
The research objective is to analyze and test the effect of Firm Size, Growth Opportunity and Net Working Capital on Firm Value through Cash Holding. The population in this study were various industrial sector companies listed on the IDX in 2019-2022. The sampling technique used is non probability sampling using purposive sampling technique. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The direct hypothesis test results show that Firm Size has a negative but insignificant effect on the Cash Holding variable, Growth Opportunity has a significant positive effect on the Cash Holding variable, Net Working Capital has a significant positive effect on the Cash Holding variable, Firm Size has a positive but insignificant effect on the Firm Value variable, Growth Opportunity has a positive but insignificant effect on Firm Value, Net Working Capital has a negative but insignificant effect on the Firm Value variable, Cash Holding has a significant negative effect on the Firm Value variable, Firm Size has a positive but insignificant effect on the Firm Value variable through Cash Holding, Growth Opportunity has a negative but insignificant effect on the Firm Value variable through Cash Holding, Net Working Capital has a negative but insignificant effect on the Firm Value variable through Cash Holding.